Modeling methods and model for flow-based IP network - WANG Ying; MENG Luo-ming; QIU Xue-song; WANG Zhi-li (Tongxin xuebao)
The management information modeling methods of IP network was studied based on the concept of "flow", which describes the connectionless characteristics of IP network. The basic principles of information modeling were promoted, the characteristics of IP network as well as the concept of "flow" were analyzed, and the transform mecha-nisms from connectionless functional architecture components to IP network managed object classes were discussed. Based on the above methods, a management information model was built, which focuses on the network level character-istics of IP network. The model had been applied in the IP network management environment and proved effective.